Ð’Ð¿Ð»Ð¸Ð² Ð³Ð¾Ñ€Ð¼Ð¾Ð½Ð°Ð»ÑŒÐ½Ð¸Ñ… Ñ–Ð½'Ñ”ÐºÑ†Ñ–Ð¹ Ð½Ð° Ð¿Ð°Ñ€Ð°Ð¼ÐµÑ‚Ñ€Ð¸ ÑÐºÐ¾ÑÑ‚Ñ– Ñ‚Ð° ÐºÑ€Ñ–Ð¾Ñ€ÐµÐ·Ð¸ÑÑ‚ÐµÐ½Ñ‚Ð½Ñ–ÑÑ‚ÑŒ ÑÐ¿ÐµÑ€Ð¼Ð°Ñ‚Ð¾Ð·Ð¾Ñ—Ð´Ñ–Ð² Ð±Ñ–Ð»Ð¾Ð³Ð¾ Ñ‚Ð¾Ð²ÑÑ‚Ð¾Ð»Ð¾Ð±Ð¸ÐºÐ° (Hypophthalmichthys molitrix, Val. 1844) - Butskyi, Kyrylo I.; Puhovkin, Anton Yu.; Kopeika, Eugeniy F. (Publishing House ‘Akademperiodyka’ of the National Academy of Sciences of Ukraine; Institute for Problems of Cryobiology and Cryomedicine, 2014)
The influence of different hormonal stimulation of final stages of gametogenesis in silver carp (Hypophthalmichthys molitrix, Val. 1844) on the quality of its sperm was studied. Preparations were used in following dosage: pituitary – 2.5 mg/kg; Surfagon – 1 mg/kg combined with Metoclopramide – 5 mg/kg; Ovopel – 0.5 pellet/kg. It was found that after stimulation of sires with a mixture of Surfagon and Metoclopramide the cell concentration in semen was higher than after stimulation by drug Ovopel or carp pituitary, and it was (9.7 ± 0.9); (10.7 ± 0.8); (13.3 ± 0.9) bln/ml, correspondingly. The ATP concentration in sperm after stimulation by this drug also was almost twice bigger and it was (51.9 ± 2.1) nmol/mg protein, and in case of Ovopel and carp pituitary it was (18.5 ± 0.7) and (30.3 ± 4) nmol/mg protein. A higher concentration of active motile spermatozoa after cryopreservation may indicate a relatively high quality of the sperm. Probl Cryobiol Cryomed 2014; 24(2):140-148.